Collapse potential and ultrasonic pulse velocity of loess soils after treatment with expanded perlite and metakaolin - Mohammad Ali Khodabandeh; Katalin Kopecskó; Gábor Nagy (Acta Polytechnica CTU Proceedings)
Collapsible soils, including loess, can support heavy loads at their natural humidity but then collapse rapidly and lose a substantial volume when the humidity increases. Soil collapse potential at different immersion stresses was investigated according to ASTM D5333. Different immersion stresses, including 100, 200, 300, 400, and 500 kPa, were used to evaluate the stress-strain behavior of soils before and after saturation. The results indicated that soil collapse potential rose with a raising of immersion stress, resulting in the highest soil collapse potential at 500 kPa immersion stress. Furthermore, the effectiveness of expanded perlite and metakaolin in treating loess soils was examined. The results revealed that the soil collapse potential reduced with an increase in perlite and metakaolin up to 8 %. Also, perlite had a more significant impact on the soil collapse potential than metakaolin. The interlocking force between soil particles was enhanced as the perlite quantity rose, and perlite prohibited soil particles from slipping on each other. Metakaolin decreased the soil collapsibility due to the pozzolanic and chemical reactions which increased particle bonding. The ultrasonic pulse velocity of soils decreased as the percentage of perlite increased. Because the perlite was not spread homogeneously, and the waves can be stuck in the heterogeneities, Metakaolin acted as a filler and increased the ultrasonic pulse velocity of the soils.